Nanostructured ZnO produced from ZnTe for random laser applications - Zalamai, Victor (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2010)
We propose to produce ZnO nanostructured material by thermal treatment in oxygen ambient of bulk ZnTe crystals and nanowires obtained by electrochemical treatment. Bulk ZnTe crystals are transformed into granular ZnO media by thermal treatment in a range of 700–800°C. This technology ensures a high optical quality of the produced ZnO nanostructured material to act as a gain medium for stimulated emission in the ultraviolet spectral region. The produced structures are expected to find applications in microlaser technologies for optoelectronics and photonics.